KNOWLEDGE MANAGEMENT CONCEPTS: a systematic review of Brazilian literature - Pomim Valentim, Marta Ligia [UNESP] (Univ Federal Campina Grande, 2020)
The concepts present in the Brazilian literature on knowledge management and its constitutive elements are presented. The international literature offers a significant amount of texts that address the conceptions, concepts and definitions about knowledge management, however, this article focuses only on the literature produced by Brazilian researchers, published in national journals, in order to know the state of the art on management knowledge and observe the evolution of the concept over time in the country. As methodological procedures, the Systematic Literature Review was defined, applying a research protocol, in order to meet the scientific rigor for the collection and analysis of data. From the analysis of the recovered texts, it was possible to know the concepts attributed to knowledge management, as well as the most significant constitutive elements in the view of Brazilian researchers.
Keywords: Knowledge management; Concepts; Knowledge sharing; Systematic Literature Review; Brazil